2006
DOI: 10.1002/ijc.21942
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of the invasion phenotype of uveal melanoma tumour cells shows the presence of MUC18 and HMG‐1 metastasis markers and leads to the identification of DJ‐1 as a potential serum biomarker

Abstract: Uveal malignant melanoma (UM) is the most frequent primary intraocular tumour in adult humans. Because the survival rate of patients with UM has changed little in the past few decades, a better understanding of the molecular events governing UM development and the identification of markers indicating the potential for metastasis at the time of diagnosis are necessary to design improved and more specific treatments. In this study, we investigated UM tumour development by comparing two recently established UM cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 50 publications
(52 reference statements)
6
79
0
Order By: Relevance
“…A potential use of serum DJ-1 as a tumor marker has been suggested in some cancers (12,37). Together with the results in the present study, serum DJ-1 is an attractive target to be studied for its potential use as a noninvasive biomarker for ESCC progression and prognosis.…”
Section: Dj-1 Is An Independent Predictor For Escc Patientsupporting
confidence: 75%
“…A potential use of serum DJ-1 as a tumor marker has been suggested in some cancers (12,37). Together with the results in the present study, serum DJ-1 is an attractive target to be studied for its potential use as a noninvasive biomarker for ESCC progression and prognosis.…”
Section: Dj-1 Is An Independent Predictor For Escc Patientsupporting
confidence: 75%
“…Two other genes, which have been linked to PD, are DJ-1 and ATP13A2. We did not determine the status of expression of DJ-1 in tissues ranging from nevi > advanced melanoma, but a histopathological study has shown that, in cutaneous melanoma, cytoplasmic expression of DJ-1 is decreased (21), whereas in the serum of patients with metastatic uveal melanoma it is elevated (22,23). To date, it is not known whether ATP13A2 plays a role in melanoma, but in light of its putative interplay with α-synuclein (24), it is noteworthy that the ATP13A2-specific dataset from our previously conducted whole-genome expression profiling study indicates that, as in the case of SNCA, the ATP13A2 gene is upregulated with progression from nevi > melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…DJ-1 was originally identified as a putative oncogene (58) and has been shown to be a negative regulator of the tumor suppressor PTEN (59). Pardo et al discovered DJ-1 as a potential serum biomarker for uveal malignant melanoma (60). SOD-1 has been shown to exert variable roles in cancer cells: overexpression of SOD-1 inhibited breast cancer cell growth and invasion (61) …”
Section: Discussionmentioning
confidence: 99%